Design, Validation, and Reliability of Survey to Measure Knowledge of Nutrition, Weight Control and its Risks - Andrea Visiedo; Jillian E. Frideres; José M. Palao (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2017)
The purpose of this study was to design, validate, and test the reliability of an instrument to evaluate knowledge of nutrition, weight control and its risk. The instrument collects information regarding: socio-demographics and athletic status; basic knowledge of nutrition (the diet they follow, nutrients, supplements, energy balance, myths, hydration and habits); and weight control and risks (weight control, eating behaviors, and weight control habits). The design, validation, and testing of the reliability of the questionnaire were done in four phases: a) design and development of the instrument, b) content validation, c) instrument reliability, and d) concurrent validity. The results show that the instrument is suitable for measuring nutrition, weight control and risk knowledge in athletes. The instrument that was developed and validated in this paper can contribute to assessing how the athletes evolve through their different formation stages.